The Role of the Nature of Advocacy in Recognition of Its Distinct Examples in Civil Code - mohammad mahdi azizollahi; Sayyid Mahdi Dadmarzi; ALI JAVADIEH (آموزه‌‌های فقه مدني, 2024)
Although Articles 656 and 657 of the Civil Code of the Islamic Republic of Iran have ruled that advocacy is a contract, the provisions of Article 680 and Article 681 can be considered contradictory to advocacy as contract. The cause of conflict in these articles can be found in the absence of explaining the nature of the legal institution. It can be concluded by examining the existing opinions, that all possible legal natures have been attributed to the advocacy institution. Some have considered it to be a contract, some have called it unilateral legal act, some have considered it to be something between a contract and unilateral legal act, and some have considered it to be a compound unilateral legal act. It was concluded in the present paper that each of the owners of the above opinions has looked at advocacy and considered that case as the nature of the advocacy, while it seems that advocacy has a comprehensive value (up to the comprehensive) that can hold contractual, unilateral legal act and even non-initiative instances. It is possible to consider advocacy due to this recognition as having a single meaning that has many examples. The conflict between the articles of the Civil Code concerning advocacy will be resolved in this way and various instances of advocacy can be identified in law.